Nicht-stabilische Halbgruppe von Mikrobündeln - Matuzevičius, A. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. И. Матузявичюс. Нестабильная полугруппа микропучков A. Matuzevičius. Nestabilus mikroišsluoksniavimų pusgrupis